THE MODEL OF OPERATIONAL FUNCTIONING OF A BATTALION TACTICAL GROUP OF THE NATIONAL GUARD OF UKRAINE DURING PARTICIPATION IN STABILIZATION ACTIONS - Butuzov, Vitalii (Honor and Law, 2025)
The content of the stages of the model of functioning of a battalion tactical group of the National Guard of Ukraine during its participation in stabilization actions is proposed and substantiated. The scientific novelty of the model lies in the fact that, unlike existing ones, it is based on a systems approach that combines simulation and scenario-based modeling. These elements determine the requirements for the functional and numerical composition of the temporary formation of the National Guard of Ukraine, as well as specific elements of the planning process (military decision-making) at the operational level according to NATO standards. This enhances the flexibility and effectiveness of battalion tactical groups during stabilization activities. The model implements a method for determining the rational composition of battalion tactical groups of the National Guard of Ukraine for participation in stabilization actions, which enables optimal allocation of forces and assets under conditions of resource constraints and potential risks that may negatively affect the operational environment and the achievement of planned results.